2012
DOI: 10.1111/j.1475-4754.2012.00702.x
|View full text |Cite
|
Sign up to set email alerts
|

Isotopes on the Beach, Part 1: Strontium Isotope Ratios as a Provenance Indicator for Lime Raw Materials Used in Roman Glass‐making

Abstract: The provenancing of Roman natron glass is one of the most challenging problems in the field of archaeometry. Although the use of Sr and Nd isotope ratios and trace element signatures as an indication of provenance has proven promising, there are still many unknowns. In this study, the influence of the different raw materials on the final Sr isotopic composition of Roman natron glass is examined. It is shown that the 87Sr/86Sr ratio in natron glass is significantly influenced by the silicate fraction of the san… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(41 citation statements)
references
References 36 publications
3
38
0
Order By: Relevance
“…Sr in natron glass is mostly derived from the shell or limestone introduced (whether or not deliberately) as the source of lime (Wedepohl and Baumann, 2000;Freestone et al, 2003;Brems et al, 2013a). High Sr concentrations in glass suggest the use of shell fragments, while low Sr contents indicate the use of limestone.…”
Section: Limementioning
confidence: 99%
See 3 more Smart Citations
“…Sr in natron glass is mostly derived from the shell or limestone introduced (whether or not deliberately) as the source of lime (Wedepohl and Baumann, 2000;Freestone et al, 2003;Brems et al, 2013a). High Sr concentrations in glass suggest the use of shell fragments, while low Sr contents indicate the use of limestone.…”
Section: Limementioning
confidence: 99%
“…B, P and U are partly derived from the silica source (Shortland et al, 2007), but they also come in with the natron flux. Sr is provided by both the sand (i.e., mostly feldspar and mica) and the source of lime (Brems et al, 2013a). In Mn-rich glasses, some of the Sr may be introduced through the Mn ore (Ganio et al, 2012b, c).…”
Section: Sandmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies have demonstrated the great potential of isotopic analysis for glass provenance study in the case of Roman, Late Antique and Byzantine glass [22,[37][38][39][40].…”
Section: Isotopic Analysismentioning
confidence: 99%